1972
DOI: 10.1037/h0033723
|View full text |Cite
|
Sign up to set email alerts
|

Balance, agreement, and attraction in pleasantness, tension, and consistency ratings of hypothetical social situations.

Abstract: Eighty-four subjects rated eight hypothetical situations for pleasantness, tension, and consistency on 9-point scales. The situations were of the personother-object (P-O-X) type, consisting of two persons and an unspecified but important "thing." The situations varied in terms of the liking relation between P and O (positive or negative) and the presence or absence of agreement concerning X. Intercorrelation of the ratings indicated that the subjects tended to regard as unpleasant the same situations that they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…The contact interpretation cannot account for such a difference, and it is clear that any totally adequate interpretation of the attraction and agreement effects must be able to explain their differential magnitudes. Second, consistent with indications from earlier studies (Crockett, 1974;Gutman and Knox, 1972;Gutman, Knox and Storm, 1974;Miller and Norman, 1976) that pleasantness scales reveal larger attraction and agreement effects than do consistency and/or expectancy scales, Insko and Adewole (1979) found in two separate studies that ratings on affective scales (pleasantness and harmony) yield larger attraction and agreement effects than do ratings on relatively more cognitive scales (expectancy, consistency and stability). Again, there is no obvious way in which the contact interpretation of the attraction and agreement effects can account for such results.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The contact interpretation cannot account for such a difference, and it is clear that any totally adequate interpretation of the attraction and agreement effects must be able to explain their differential magnitudes. Second, consistent with indications from earlier studies (Crockett, 1974;Gutman and Knox, 1972;Gutman, Knox and Storm, 1974;Miller and Norman, 1976) that pleasantness scales reveal larger attraction and agreement effects than do consistency and/or expectancy scales, Insko and Adewole (1979) found in two separate studies that ratings on affective scales (pleasantness and harmony) yield larger attraction and agreement effects than do ratings on relatively more cognitive scales (expectancy, consistency and stability). Again, there is no obvious way in which the contact interpretation of the attraction and agreement effects can account for such results.…”
Section: Introductionsupporting
confidence: 80%
“…This was done some time ago by Insko (1967). More recently, Gutman and Knox (1972), Crockett (1974), and Willis and Burgess (1974) have made the same or similar points.…”
Section: Introductionmentioning
confidence: 89%
“…Gutman and Knox (1972) showed that their pleasantness ratings data gave greater evidence of positivity and agreement biases, than of balance. A similar experiment by Whitney (1971) indicated agreement and positivity biases but not a balance bias.…”
Section: (1) a Classification Of Experiments Concerned With Balance Tmentioning
confidence: 95%
“…In addition, a positivity bias on the P/O relation appears to be fairly pervasive, so that triangles containing P/ 0 positive are seen as more pleasant than those containing P/ 0 negative (e.g. Gutman and Knox, 1972;Jordan, 1953;Rodrigues, 1967;Whitney, 1971). Further, the P/O relation is more easily learned when it is positive (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation